Madagascar : smiley island [videorecording (DVD)] - Huot, Jadrino; Roberge, Annie-Claude; Roberge, Annie-Claude; Lalone, Francis (Passport to the world., 2019)
Madagascar is a synonym for biodiversity and is one of the richest regions on the planet in terms of fauna and flora, with a host of endemic species, including the famous lemurs. Culture and traditions are also deeply rooted in the hearts of Malagasies, who scorn the difficulties of day-to-day life and always wear their brightest smiles.